El nivel de cumplimiento de las actividades del plan operativo para medir la gestión de calidad en la subgerencia de tesorería de la municipalidad provincial de Trujillo en el periodo 2014 – 2016 - Rodríguez Philipps, Kenny Rene (2018)
The objective of this study was to determine the level of compliance of the activities of the Operational Plan to measure Quality Management in the Treasury Sub-Department of the Provincial Municipality of Trujillo in the period 2014-2016. The population includes the operational plans, the reports of self-evaluation and the reports of execution of budgets and expenses of the MPT of the years 2014, 2015 and 2016; and the reports generated for the Treasury area of the MPT of those years were taken as a sample. The design of this research is non-experimental, transversal and descriptive and the technique used was the Documentary analysis._x000D_ The research hypothesis is rejected, that is, the level of compliance with the activities of the Operational Plan to measure Quality Management in the Treasury Sub-Department of the Provincial Municipality of Trujillo is not at a high level in the period 2014-2016. However, it is observed that more than 80 percent of the institutional activities of the Treasury Department of the Provincial Municipality of Trujillo have an efficiency level greater than 80%, so it is inferred that the level of compliance with Institutional Activities in global it is at a medium level for that period. It is concluded that of the 14 institutional activities of the 2014 POI, there is an effectiveness of 99.5%, an efficiency of 99.5% and an efficiency of 109.9%. It is also observed that 4 activities did not achieve the goal; while of the 14 institutional activities of the 2015 POI, it showed an effectiveness of 83.7%, an efficiency of 83.7% and an efficiency of 100.5%. It is also observed that 8 activities did not achieve the goal; and For the 2016 POI, an effectiveness of 99.2%, an efficiency of 99.2% and an efficiency of 102.5% are observed. It is also observed that 6 activities did not achieve the goal